A Recommendation on Themes for Teaching Urban Public Finance Course - Patta, Jhonny (Center for Research and Community Services ITB, 2007)
This article recommends the themes that ﬁt to be the syllabus of teaching urban public ﬁnance. They are derived from the standard literatures in pubiic finance. Five themes are identifird namely microeconomic rational of urban public ﬁnance, public choice of ﬁscal policy, fiscal federalism, urban policy revenue resources, and budgeting and financial analysis. While ﬁnancing development is a sin qua non theme for developing countries, adjustment will be needed to fit the context of the countries.Keywords: urban, public finance, classic readings